2018
DOI: 10.3390/systems6040043
|View full text |Cite
|
Sign up to set email alerts
|

Could Education for Sustainable Development Benefit from a Systems Thinking Approach?

Abstract: Sustainable development is not a novel concept. However, we continue with our unsustainable way of living. It is as though we cannot see our own part in the unsustainable system. Values, ethics and morals are connected to education and therefor education is in a key position to change the way we think and act for a sustainable future. Both education for sustainable development (ESD) and systems thinking are concepts connected to changes toward a sustainable future. However, they have proven to be conceptually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
0
39
0
1
Order By: Relevance
“…This work has analysed some of the main difficulties of pre-service teachers in the construction of relationships between sustainability and their lifestyle during an educational intervention, focused on the problem-based learning approach and, more specifically, on the resolution of socio-ecological problems in their surroundings. This approach could promote a systemic vision to interpret the causes and consequences in the different environmental, social and economic dimensions [6, 11,44], basic for EDS [12,77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work has analysed some of the main difficulties of pre-service teachers in the construction of relationships between sustainability and their lifestyle during an educational intervention, focused on the problem-based learning approach and, more specifically, on the resolution of socio-ecological problems in their surroundings. This approach could promote a systemic vision to interpret the causes and consequences in the different environmental, social and economic dimensions [6, 11,44], basic for EDS [12,77].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the public's understanding of the importance of BD conservation seems to have declined significantly during the past decades [3,9]. In this sense, Hofman-Bergholm [12] (p. 7) suggested that a 'kind of ecological illiteracy has developed' among the population and, even, among university graduates. This implies that knowledge of some key cognitive skills for the analysis of environmental problems and skills in the use of environmental action strategies may yet be limited [15,23].…”
Section: The Close Relationship Between Our Lifestyle and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research about Nordic student teachersí views on the relationship between species identication, biodiversity and sustainable development Palmberg, Berg, Jeronen, K‰rkk‰inen, Norrgård-Sillanp‰‰, Persson, Vilkonis, & Yli-Panula, 2015;Palmberg, Jonsson, Jeronen, & Yli-Panula, 2016) implies that Nordic student teachers possess low levels of ecological knowledge and species identification. The importance of integrating systems thinking into education has been emphasized in order to promote an understanding of the complex nature of sustainability (Hofman-Bergholm, 2018;Palmberg et al, 2017;WWF, 2016;Lewis et al, 2014;Sterling, 2003). However, according to Palmberg et al (2017), Nordic student teachers do not seem to develop any form of systems thinking during their teacher education.…”
Section: Research On Different Educational Levels In Finlandmentioning
confidence: 99%
“…The problem in Finland, however, is that the universities are autonomous and can decide for themselves where to focus within the education. This means that the leaders of universities will play a major role if education for sustainable development is to be implemented within teacher education in Finland (Wolff et al, 2017;Hofman-Bergholm, 2018).…”
Section: Teacher Education Takes Place At Universitiesmentioning
confidence: 99%